2020
DOI: 10.1111/pim.12812
|View full text |Cite
|
Sign up to set email alerts
|

Glycan moieties in Entamoeba histolytica ubiquitin are immunodominant

Abstract: The ubiquitin‐proteasome system plays a central role performing several functions to maintain parasite homeostasis. We have reported the partial characterization of N‐linked glycosylation profile in E. histolytica ubiquitin (EhUb). Here we examined the immunogenicity and antigenicity of carbohydrates in EhUbiquitin. Rabbits were immunized with purified EhUbiquitin or purified recombinant rUb expressed by E. coli. Using Western Blot, we explored the immunogenicity and antigenicity of protein portion and carbohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In a previous study, we found antibodies to Ehub in the sera of six patients with invasive amoebiasis. 9 This was unexpected because ubiquitin is an evolutionarily conserved molecule with high sequence similarity between species; the E. histolytica ubiquitin differs in only six amino acid residues from the homologue consensus in humans and lower organisms. 20 To rule out a fortuitous finding, we decided to expand our study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, we found antibodies to Ehub in the sera of six patients with invasive amoebiasis. 9 This was unexpected because ubiquitin is an evolutionarily conserved molecule with high sequence similarity between species; the E. histolytica ubiquitin differs in only six amino acid residues from the homologue consensus in humans and lower organisms. 20 To rule out a fortuitous finding, we decided to expand our study.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli expressing recombinant ubiquitin from E. histolytica HM-1: IMSS rEhub was obtained as we reported previously. 9 Briefly, RNA isolated from axenic E. histolytica HM-1: IMSS trophozoites were used for cDNA synthesis. The PCR product was cloned and expressed in Escherichia coli BL21 transformed with pET-28a vector containing the Ehub protein fused with 6X Histidine tag.…”
Section: E Histolytica Recombinant Ubiquitinmentioning
confidence: 99%
See 3 more Smart Citations